AB0494 Systemic sclerosis and cancer risk: our experience. (23rd January 2014) - Lanciano, E.; Praino, E.; Rotondo, C.; Covelli, M.; Iannone, F.; Lapadula, G.
Abstract : Background: A higher incidence of cancer in Systemic Sclerosis (SSc) patients compared with the general population has been suggested by several observational studies reporting, however, different estimates. A recent meta-analysis has shown that, compared with the general population, the global relative risk (RR) to develop all invasive cancers in SSc patients was 1.75 (95% CI 1.41-2.18). Analysis of the single cancer sites indicated a strong association with lung cancer (RR 4.35; 95% CI 2.08-9.09), and a significant increased RR for hematologic neoplasms (RR 2.24; 95% CI 1.53- 3.29). The relation with breast cancer, previously reported by some epidemiological studies, was not confirmed (RR 1.05; 95% CI 0.86, 1.29). The aim of this study was to determine whether the incidence of cancer is increased among SSc patients in our center. Methods: The study subjects consisted of 190 patients who had been consecutively evaluated between January 2008 until December 2012. We retrospectively reviewed their medical records and investigated the incidence rate of cancer. Results: Eight out of 190 patients developed cancer (all females). The average age at diagnosis of cancer was 55, 3 years. The types of cancers were: 3 Hodgkin Lymphoma (LnH), 1 Multiple Myeloma, 1 leukemya, 1 lung cancer, 1 colon cancer, 1 breast cancer. The overall rate of cancer in our SSc cohort was 3, 7%, instead in Italian population is 4%. However, LnH rate was 37.5% of cancers, but its prevalence is 4-5% of cancer cases in general population. Therapy, autoantibodies, smoking, and lung involvement were not significantly different between SSc patients with or without cancer. Conclusions: In our SSc patients, cancer prevalence was similar to that of Italian population. Hematologic cancers were more frequent than others. These data suggest that screening for cancer should be carried out in SSc like in general population, but that for blood cancer is strongly recommended in SSc, probably because of hyperactivation of the immune system. Further investigations are warranted to confirm these preliminary data and to understand the relationship between blood cancer risk and SSc. References: Rheumatology (Oxford). 2013 Jan;52(1):143-54. doi: 10.1093/rheumatology/kes303. Epub 2012 Nov 22. Systemic sclerosis (scleroderma) and cancer risk: systematic review and meta-analysis of observational studies. Bonifazi M, Tramacere I, Pomponio G, Gabrielli B, Avvedimento EV, La Vecchia C, Negri E, Gabrielli A. Source Istituto di Clinica Medica, Dipartimento di Scienze Cliniche e Molecolari, Università Politecnica delle Marche, Via Tronto 10/A, 60100, Ancona, Italy. a.gabrielli@univpm.it. Disclosure of Interest: None Declared